A taxonomic survey of marine brachyuran crabs in Lapinig Bay, Northern Samar. - Robles, Lady Angela M. (Lady Angela M. Robles, 2018)
The Samar islands have no inventory on brachyuran crab species. Moreover, no studies related to taxonomy of all brachyuran crabs have been conducted in Lapinig Bay, Northern Samar. Thus, this study is aimed to survey the marine brachyuran crabs present in the municipality. Brachyuran crabs were collected in accessible collecting stations within selected areas of the bay through the differences in water depth from January to March 2018.